2020
DOI: 10.3390/coatings10090847
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Superhydrophobic Wood Surface by Etching Polydopamine Coating with Sodium Hydroxide

Abstract: Superhydrophobic treatment of wood surfaces can effectively prevent the contact between the external moisture and wood, which improves the service life of the wood. In this study, different rough surfaces of wood were constructed, derived from the self-polymerization of dopamine (DA) in weak base solution to form a polydopamine (PDA) coating and the deprotonation of the PDA coating in a strong base solution. Furthermore, octadecyltrichlorosilane (OTS) was used as a low-surface-free-energy agent to modify rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Many researchers have done a lot of research on increasing the hydrophilicity and surface energy of PDMS and enhancing its adhesion and functionalization [7][8][9]. It is reported that dopamine (DA) can be codeposited into a nano-thin layer of poly(dopamine) (PDA) on the surface of the material through covalent bonds, hydrogen bonds, metal chelation, and π-π interaction under alkaline conditions, thus improving the surface energy and adhesion of the material [10][11][12]. Although acrylic acid, etc., can also be used as co-deposited coatings to improve surface energy and adhesion, the process is mostly time-consuming, relies on relatively complex setups, and is often limited to certain substrate chemistries and types of target molecules [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have done a lot of research on increasing the hydrophilicity and surface energy of PDMS and enhancing its adhesion and functionalization [7][8][9]. It is reported that dopamine (DA) can be codeposited into a nano-thin layer of poly(dopamine) (PDA) on the surface of the material through covalent bonds, hydrogen bonds, metal chelation, and π-π interaction under alkaline conditions, thus improving the surface energy and adhesion of the material [10][11][12]. Although acrylic acid, etc., can also be used as co-deposited coatings to improve surface energy and adhesion, the process is mostly time-consuming, relies on relatively complex setups, and is often limited to certain substrate chemistries and types of target molecules [13].…”
Section: Introductionmentioning
confidence: 99%
“…Wood is a popular material for furniture and floor manufacturing as well as other industries since it is inexpensive, simple to produce, beautifully patterned, naturally renewable, and low-carbon [ 44 , 72 , 73 , 74 , 75 ]. However, wood cell walls are composed of cellulose, etc., and the hydroxyl groups on its branch chains combine with water to create hydrogen bonds, resulting in the wood itself being significantly hydrophilic [ 76 , 77 ]. It is prone to corrosion in a humid environment, resulting in cracking, mildew, greatly reducing the durability of wood, resulting in resource waste, and economic losses [ 78 , 79 , 80 ].…”
Section: Improvement Of Hydrophobicity Of the Wood Surfacementioning
confidence: 99%
“…Meanwhile, the application of superhydrophobic modification for wood is proposed to overcome the above challenges. The wood surface was endowed with unique wettability and improved the functional properties, such as water resistance, dimensional stability, etc., which further broadens wood multifunctional usage (Yi et al 2020).…”
Section: Introductionmentioning
confidence: 98%